Modeling and Simulation Study of Downdraft Gasifier Using Oil-Palm Fronds - Mekbib, S. (2009)
Gasification of biomass provides clean and combustible gas with sufficient energy, which can be used for electricity generation, engine etc. However, successful design and operation of gasifiers are not simple. There are no neat rules as the thermodynamics of gasifier operation are not well understood. In this paper, a preliminary study of the operation and performance of downdraft biomass gasifier using oil palm fronds is carried out. The performance study is partially carried out using ASPEN PLUS process simulator software for modeling and simulating the various zones of the gasification process (drying, pyrolysis, oxidation and reduction). As ASPEN PLUS does not have a built-in gasifier model, a combination of the various reactors of the simulator are used to model the gasification processes. This model is used to predict the producer gas composition for different operating temperatures, pressure and air-fuel ratio. In addition a primary experiment is carried out to determine the feasibility of OPF as a gasification feedstock. From the simulation study it is shown that higher mass fraction of CO and CH4 can be obtained at lower Air-Fuel ratio, and lower pressure (below 5bar). The mass fraction of CO increases sharply with increase in the oxidation zone temperature, for the range 500-700°C.